(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
In this article, you will find various computational problems and exercises, as well as how to work them, as well as suggestions for working on topics related to food chains or ecological pyramids. presented, problem solving in these topics is integrally related to the extent to which theoretical knowledge has been mastered. If the student does not have the necessary theoretical knowledge of the food chain or ecological pyramids, he will not be able to solve any problem or exercise independently. Therefore, some of the information needed to solve food chain problems is explained in a simple form